Strategi Laporan Keuangan Dalam Memperoleh Opini Wajar Tanpa Pengecualian (WTP) Di Baznas Kabupaten Jember Tahun 2021 - Sugianto, Sugianto; Amin, Mokhamad Syahrul (Fakultas Syariah IAIN Kerinci, 2023)
BAZNAS Jember has just undergone an audit process for the first time and its financial statements are relatively new. However, the audit has achieved excellent results by obtaining evidence of WTP opinion from the public accounting firm. This success gives confidence to the public that the management of zakat in BAZNAS Jember is running well and can be trusted. The purpose of this research focuses on the scope, namely how the Financial Report Strategy in Obtaining an Unqualified Opinion (WTP) at BAZNAS Jember Regency in 2021 and how the BAZNAS Jember Financial Report Form in 2021. This research uses a qualitative approach with descriptive research. In determining informants, researchers used purposive techniques. While data collection techniques using observation, interviews, and documentation. The results of this study are first, BAZNAS Jember has a strategy in preparing its financial statements with the aim of obtaining WTP opinion. This strategy involves three stages, namely planning, implementation, and evaluation, which are carried out to ensure the quality and accuracy of the financial statements prepared. Second, BAZNAS Jember's financial statements in 2021 were prepared using PSAK No. 109 financial standards, which consist of five main parts, namely the statement of financial position, statement of changes in funds, statement of changes in assets under management, statement of cash flows, and notes to the financial statements.